Implementation of BPS RESTful API on Flutter-Based DALEM Mobile Application for Statistical Data Access Efficiency - Aan Kia Asshifa; Bambang Agus Herlambang; Khoiriya Latifah; M Abdul Muhshi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
This study addresses the urgent issue of inefficient access to statistical data on the official BPS-Statistics Indonesia, Demak Regency website, particularly under conditions of increasing data volume and limited network stability. Users frequently experience slow response times and high data consumption due to complex web rendering and excessive network requests, which hinder timely access to critical information for decision-making. Therefore, this research aims to implement the RESTful API on the Flutter-based DALEM mobile application to improve the efficiency of access to BPS-Statistics Indonesia, Demak Regency statistical data. The method used is Research and Development (R&D) with the ADDIE model, accompanied by comparative experimental testing of the official BPS website system. Evaluation parameters include response time, number of requests, and data transfer efficiency. The test results showed that mobile applications have an average response time of 437-826 ms with 1-10 requests per scenario, while websites require 1,368-1,790 ms with 80-91 requests. Quantitatively, mobile applications showed an increase in access time efficiency of more than 50% and a reduction in the number of requests by up to 88%. These findings prove that the JSON-based RESTful API architecture combined with Asynchronous programming on Flutter is able to significantly optimize client-server communication in regional statistical data services.